Factors Affecting Profitability of General Insurance Companies in Indonesia - Maulana, Denny; Mulyana, Bambang (The Economics and Finance Letters, 2020)
This research work shows the impact on profitability by Return on Assets (ROA) on capital adequacy measured by Risk Based Capital (RBC), Return on Investment (ROI) and Solvency by Debt Equity Rate (DER) measured). Then prove the RBC and ROI effect on DER, then demonstrate the RBC 's influence on ROA through DER, demonstrate the ROA impact on the general insurers reported upon on Indonesian Stok Exchange 2015-2018. The design of the research was causal research. Technical sampling using a deliberate method of sampling. During the four-year observation period, eight companies were obtained using this method that met the criteria of 14 companies. 32 samples in total. Study of linear regression model and path analysis is utilized in data analysis process. ROI has a positive and significant ROA effect, and DER has an adverse effect and important to ROA; The report's result shown that RBC has no significant ROA impact. Then RBC has an impact on DER, but ROI has a positive and important effect on DER. RBC via DER then has no significant impact on ROA, whereas ROI via DER has a positive and substantial impact on ROA. RBC has a significant negative effect on DER, and ROI has a significant and positive effect on DER. Then RBC by DER does not have a significant ROA effect, while ROI by DER has a positive and significant ROA impact. RBC then has a significant negative impact on DER, while ROI has a positive and important impact on DER.